Study of Plastic Making on Polyblend Methylacrylate-Starch - Istiroyah Istiroyah; Lailatin Nuriyah; N. Ardian P (Natural B, Journal of Health and Environmental Sciences, 2011)
The aims of the research were to make biodegradable plastics starch-methyl acrylate. FTIR spectra showed that polymerization of 100 grams of starch with 2 L of water at 95ºC and added by 150 grams of methyl acrylate at 40-45ºC with ceric ammonium nitrate as catalyst, produced polyblend plastics. Tensile strength of plastics depends on starch type. Biodegradable plastics with starch that have high amylase concentration showed high tensile strength. Plastic sweet potato starch had maximum tensil strength at 18.6±4.4 Mpa while maximum elongation at bread was at 25.33±6.29% from plastic madeform corn strach.